2010
DOI: 10.1074/jbc.m110.130518
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ/BMP Type I Receptors ALK1 and ALK2 Are Essential for BMP9-induced Osteogenic Signaling in Mesenchymal Stem Cells

Abstract: Mesenchymal stem cells (MSCs) are bone marrow stromal cells that can differentiate into multiple lineages. We previously demonstrated that BMP9 is one of the most potent BMPs to induce osteogenic differentiation of MSCs. BMP9 is one of the least studied BMPs. Whereas ALK1, ALK5, and/or endoglin have recently been reported as potential BMP9 type I receptors in endothelial cells, little is known about type I receptor involvement in BMP9-induced osteogenic differentiation in MSCs. Here, we conduct a comprehensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
212
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 170 publications
(222 citation statements)
references
References 52 publications
7
212
2
1
Order By: Relevance
“…Recombinant adenoviruses harboring dominant-negative forms of ALK1, ALK2, BMPRII, ActRII were generated as previously described (8,9). Recombinant adenoviruses expressing siRNA targeted Smad4 (AdR-si-Smad4), p38 (AdR-si-p38), ERK1/2 (AdR-si-ERK1/2) were kindly provided by Dr. Tong-chuan He of University of Chicago Medical Center.…”
Section: Construction Of Recombinant Adenovirusesmentioning
confidence: 99%
See 3 more Smart Citations
“…Recombinant adenoviruses harboring dominant-negative forms of ALK1, ALK2, BMPRII, ActRII were generated as previously described (8,9). Recombinant adenoviruses expressing siRNA targeted Smad4 (AdR-si-Smad4), p38 (AdR-si-p38), ERK1/2 (AdR-si-ERK1/2) were kindly provided by Dr. Tong-chuan He of University of Chicago Medical Center.…”
Section: Construction Of Recombinant Adenovirusesmentioning
confidence: 99%
“…Recent studies have indicated that BMP9, one of the least studied BMPs, is a more potent inducer in promoting osteogenic differentiation of MSCs (6)(7)(8)(9). Further expression profiling analysis has identified several important signaling mediators of BMP9 in MSCs (7).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For BMP-2 and -4 -10, signalling is mediated by the type I receptors (BMPR-IA or IB) whereas the BMP-5/-6/-7 subgroup utilizes ActR-I (Alk2) for signalling (for review, see Katagiri et al [34]). For BMP-9 high affinity binding to ALK1 has been reported but signalling can also occur via ActR-I [35]. The obvious discrepancy between the number of ligands (more than 20 BMP members have been identified in mammals to date) and the limited amount of receptors raises important questions especially how these proteins can share so many different cellular functions and furthermore how those can act as morphogens during embryogenesis.…”
Section: Introductionmentioning
confidence: 99%